The contribution of the Poles to the socioeconomic development of Kazakhstan (Herald of Journalism, 2018)
Poles are one of the numerous and significant ethnic groups in Kazakhstan. The contribution ofPolish exiles such as A. Yanushkevich, S. Zagryazhsky, G. Zelisnky, M. Viner, A. Pashkovsky, M. Lukashevich,A. Zatayevich to the Kazakh culture is priceless. Thousands of Polish engineers, doctors, artworkers, hundreds of professors and scientists found appliance to their knowledge, skills and talents inKazakhstan, that were expressed in their outstanding achievements and brilliant discoveries that enrichedKazakh science, technology and culture. In the places of their residence Poles raised the agriculture ofgrain, livestock, vegetable sectors to the high level. Almost all the farms inhabited by Poles soon becamemillionaires. The achievements of Polish diaspora could become the source of scientific references.Detailed research of this issue requires thorough acquaintance with the materials stored in the archives.